Mathematical modeling and experimental results of a sandwich-type amperometric biosensor - Romero, Marcelo Ricardo (2011)
A comprehensive numerical treatment of the diffusion and reaction within a sandwich-type amperometric biosensor is presented. The model considers that the enzyme reacts according to a ping-pong mechanism and that it is entrapped into a so-called enzymatic matrix placed between two diffusion membranes. It is found that the concentrations of reagents and products within the sensor are difficult of being compared to those of the bulk. In this regard, the use of approximate analytical solutions would involve errors in the analysis of kinetic parameters corresponding to this kind of biosensors. Provided the mediator species are in high concentration or diffuse much faster than the substrate, the response time of a biosensor of this kind would be determined by the diffusion of the substrate though the external membrane. In this sense, those systems with immobilized mediators, in which diffusion of electrons or holes is assumed for the charge transport process, could be also described by this model. Thus, the thickness and the permeability to the analyte of the external membrane are critical parameters for improving the response time of a sandwich-type biosensor. The simulated curves are compared with experimental profiles corresponding to a lactate amperometric biosensor obtaining consistent results. In a future publication a non-linear fitting algorithm will be combined to the model for the extraction of kinetic and/or geometric parameters.